E-WORKSHEET EDIBLE STRAW BERBAHAN ALAM: INOVASI PERANGKAT PJBL BERORIENTASI ESD UNTUK PENGEMBANGAN LITERASI SAINS - Fadillah, Rida Nurul; Hernani, Hernani; Supriatna, Asep (Lantanida Journal, 2026)
The low level of science literacy among Indonesian students, as reflected in the 2022 PISA results with a score of 383, underscores the need for innovative, contextual, and meaningful learning materials. This study aims to develop an e-worksheet based on Project-Based Learning (PjBL) oriented toward Education for Sustainable Development (ESD) on the topic of making edible straws from natural materials as an effort to improve students’ science literacy. The method used is Design and Development Research (DDR) with three main stages: planning, production, and evaluation. Validation was conducted by four validators comprising two chemistry education lecturers and two high school chemistry teachers covering aspects of instructional alignment with PjBL syntax, grammar, layout, and content alignment with learning objectives. Validation results showed a score range of 87.50–100%, falling into the good to very good category. A limited feasibility test involved 18 12th-grade high school students divided into three groups. The results of the feasibility test showed that all PjBL syntax was implemented well, with the highest score in the monitoring stage (100%) and the lowest in the schedule preparation stage (69%). Overall, the developed e-worksheet is suitable for use as a learning tool to train students' scientific literacy in a contextual and meaningful way.